Remarks and inventions : skeptical essays about kinship - Needham, Rodney (Routledge library editions. Anthropology and ethnography., 2004)
This volume scrutinizes the questions of conceptualization, method and history in the fields of kinship, social anthropology and structuralism. It puts forward a radical revision of the conventional approaches and criteria. Exploring analysis and method in the disparity between relative age and kinship categories as means of social classification, the book makes theoretical readjustments, largely inspired by the precepts of Wittgenstein. Originally published in 1971.